Perkembangan Madrasah dan Tingkat Kepercayaan Publik - As'ari As'ari; Enung Nugraha (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Madrasah developed every decade for Indonesia society. The development of Madrasah runned along with the need of family household. Madrasah sustained the quality as well as provided more deep practices and extra-curricular to support prominent programs. This research describes deeply of madrasah development and society or public trust sustainably to madrasah. This study is descriptive qualitative research designed by naturalistic inquiry to naturalistic phenomena of Islamic education. The data collecting techniques are observation and interview by which data analytical inductive analyses, creative synthesis and holistic perspective to education phenomena and stakeholders. The result of the study shows that in modern and industrial era 4.0, stakeholders respond to what society need to industrial world rather than just believing the truth of self-sense to religious touches. The quality and public trust, on education in Madrasah, increase. Madrasah strives to improve the significant plays a role of state Madrasah as a model and as a controller of the quality of Madrasah taught. Developing educational programs and improving the ability of madrasahs to bring the role as public schools based on Islamic characteristics creates graduates’ quality as social expectations.